Autosomal recessive spinocerebellar ataxia‐20 due to a novel SNX14 variant in an Indian girl. Issue 6 (23rd February 2022) - Sait, Haseena; Moirangthem, Amita; Agrawal, Vinita; Phadke, Shubha R.
Abstract: Autosomal recessive spinocerebellar ataxia‐20 is a rare disorder having distinctive coarse facies in addition to intellectual disability and cerebellar ataxia, with less than 35 cases reported worldwide. It is caused by biallelic variants in the SNX14 gene and is classified under the group of autophagy disorders. We report a 9‐year‐old girl who presented with classic clinical features of autosomal recessive spinocerebellar ataxia‐20 and cerebellar atrophy on magnetic resonance imaging of brain. Trio exome sequencing with Sanger confirmation revealed a novel splice site variant, c.140 + 3A > T in the SNX14 gene. The variant pathogenicity established by mRNA expression study showed a significant reduction in the expression levels of SNX14 gene in proband and her parents on comparison to the control. The electron microscopy of the skin fibroblasts of proband depicted numerous cytoplasmic vacuoles with variable degrees of dense staining material. In addition, we have briefly reviewed and compared the phenotypic features of published cases of autosomal recessive spinocerebellar ataxia‐20 in the literature. Coarse facies, intellectual disability with severe speech delay, hypotonia, and cerebellar atrophy were universal findings in the published cases. This is the second reported case from the Indian subcontinent.